Novel production and characterization of porous calcium phosphate suitable for bone tissue engineering applications. Issue 3 (April 2015) - Stergioudi, F.; Choleridis, A.; Paulidou, E.; Smyrnaios, E.; Michailidis, N.
Abstract: Porous calcium phosphate materials have found enormous use in biomedical applications including hard tissue regeneration. In this study, tailored made open-cell porous calcium phosphate samples were produced by employing a novel dissolution sintering process, using crystalline raw cane sugar as a leachable pore former material. The process parameters of the production stages were properly adjusted to optimise the quality and structure of open-cell porous calcium phosphatesamples. The influence of sintering conditions on the macro and micro-structure of the resultant porous product is investigated with a view to produce high-quality and strong porous calcium phosphate samples. Preliminary in-vitro biodegradation results indicate formation of a bone-like apatite on the porous samples surface. Mechanical performance of the produced porous calcium phosphate samples is interesting and dictates their potential use as low load-bearing implants for hard tissue replacement or as filling materials and scaffolds for cancellous bone defects repairs.